Emerging trends affecting future employment opportunities for people with intellectual disability: The case of a large retail organisation. Issue 3 (3rd July 2018) - Moore, Katherine; McDonald, Paula; Bartlett, Jennifer
ABSTRACT: Background: Despite existing literature identifying the organisational drivers and constraints of employing people with disability, little research has explored how organisations embed disability-inclusive recruitment practices to facilitate ongoing employment opportunities for people with intellectual disability (ID). Method: An embedded case study methodology was used to explore how supervisors and co-workers within a large Australian retail organisation legitimise disability recruitment practices for people with ID and how different operating environments can influence ongoing employment opportunities. Results: Future employment opportunities for people with ID were limited by centralised recruitment process, the availability of suitable roles, and productivity and efficiency demands of the local operating environment, despite the presence of organisational diversity strategies supporting disability employment. Conclusions: The future employability of people with ID is influenced by technological changes to work environments and an increasing focus on efficiency. Future research should address innovative task modifications to enhance employment opportunities for people with ID.